Classical Solution to the Electropainting Problem (Journal of Partial Differential Equations, 1991)
The mathematical modelling of the electrodeposition phenomenon leads to a linear elliptic partial differential equation subject to nonlinear evolutionary mixed boundary conditions. ln this paper, the existence, uniqueness and regularity of classical solution are proved for the electropainting problem when &#8220dissolution current&#8221 is zero.